Small-Gauge Pars Plana Vitrectomy for the Management of Symptomatic Posterior Vitreous Detachment after Phacoemulsification and Multifocal Intraocular Lens Implantation: A Pilot Study from the Pan-American Collaborative Retina Study Group - Rodrigo M. Navarro; Leonardo M. Machado; Ossires Maia; Lihteh Wu; Michel E. Farah; Octaviano Magalhaes; J. Fernando Arevalo; Mauricio Maia (Journal of Ophthalmology)
Purpose. To determine the efficacy of 23-gauge pars plana vitrectomy (PPV) for symptomatic posterior vitreous detachment (PVD) on visual acuity (VA) and quality after multifocal intraocular lenses (IOLs). Methods. In this prospective case series, patients who developed symptomatic PVD and were not satisfied with visual quality due to floaters and halos after multifocal IOL implantation underwent PPV. Examinations included LogMAR uncorrected visual acuity (UCVA), intraocular pressure, biomicroscopy, and indirect ophthalmoscopy at baseline and 1, 7, 30, and 180 days postoperatively. Ultrasonography and aberrometry were performed. The Visual Functioning Questionnaire 25 (VFQ-25) was administered preoperatively and at 30 days postoperatively. Both the postoperative UCVA and questionnaire results were compared to preoperative findings using the Wilcoxon test. Results. Sixteen eyes of 8 patients were included. VA significantly improved from 0.17 to 0.09 postoperatively (P=0.017). All patients reported improvement of halos, glare, and floaters. VFQ-25 scores significantly improved in general vision (P=0.023), near activities (P=0.043), distance activities (P=0.041), mental health (P=0.011), role difficulties (P=0.042), and driving (P=0.016). Conclusion. PPV may increase UCVA and quality of vision in patients with bilateral multifocal IOLs and symptomatic PVD. Larger studies are advised.